ANALISIS BUDAYA KERJA PEGAWAI KOMISI PENGAWAS PERSAINGAN USAHA REPUBLIK INDONESIA - Amelia Siallagan; Christian Wiradendi Wolor; Eka Dewi Utari (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to describe the characteristics of the work culture among employees at the Indonesia Competition Commission (KPPU RI) using a descriptive qualitative approach. Data analysis identified patterns of values, practices, and work attitudes at KPPU RI. The findings reveal that KPPU RI's work culture is strongly characterized by a high level of professionalism, strict discipline, integrity, and accountability in carrying out duties. Employees operate within a clear structure of responsibility, although cross-divisional communication and high work pressure remain challenges. A culture of mutual support and open communication is still essential in daily activities. Employees also expect a more innovative, collaborative, efficient, and adaptive work culture that keep and adaptive work culture that keeps pace with the times, including the use of technology and flexible work arrangements.